An exploration of the influence of Femvertising on Castle Lite’s Brand Image amongst South African Female Consumers. - Ntshweng, Karabo (The IIE, 2020)
To challenge outdated gender stereotypes, contribute to female empowerment and build deeper emotional connections with female consumers, brands have made use of femvertising (Becker-Herby, 2016). One such brand is South African premium beer brand Castle Lite, which has been committed to the empowerment of women over the last couple of years (Smith, 2019). The purpose of this study was to explore the influence of femvertising on Castle Lite’s brand image amongst South African female consumers. Guided by the Affect Transfer Hypothesis theory, the study investigated consumer attitudes towards femvertising and how those attitudes ultimately influence brand. The study is qualitative in nature, and a focus group was the data collection method used, which allowed participants to give deep insight into their thoughts, feelings and attitudes towards femvertising, and how ultimately these attitudes influence Castle Lite’s brand image. The sample was made up of five Johannesburg based women aged between 24-35 who are regular Castle Lite drinkers. The results of this paper indicate that South African women have positive attitudes towards femvertising, and this form of brand activism can positively enhance the image of a brand if executed authentically and is aligned with the core values of the brand.
Keywords: Gender; Beer brand; Brand activism; Female empowerment; Gender representation; Attitude towards ad; Attitude towards brand